Studies on the effects of myricetin derivatives from Syzygium malaccense in hyperglycemia and related complications / Bavani Arumugam - Bavani, Arumugam (2016)
Diabetes mellitus is characterized by elevated blood glucose level (hyperglycemia) and this is known to cause the generation of free radicals. An imbalance between free radicals and antioxidant defense system leads to oxidative stress condition which results in oxidative damage and tissue injury: hallmark of diabetes and its complications. Numerous plants and bioactive compounds offer prudent option for treatment of diabetes and Syzygium malaccense is one of them. The aim of the present study was to investigate the potential use of S. malaccense as an anti-hyperglycemic agent and its ability to attenuate oxidative stress-induced diabetic complications using adipocyte (3T3-L1) and retinal (ARPE-19) cellular models. Bioactive compounds present in the ethanolic leaf extract of S. malaccense were determined through bioassay-guided fractionation using HPLC and LCMS analyses. Antioxidant and antiglycemic properties of samples (crude extract, active fraction and pure compounds) were assessed through radical scavenging assays and inhibition of carbohydrate hydrolyzing enzymes (α-glucosidase and α-amylase), respectively. Antiglycative property of the samples was determined through inhibition of advanced glycation end product (AGE) formation. Oxidative stress was induced in ARPE-19 cells using high glucose (HG; 30 mM) or glucose oxidase (GO). GO catalyzes hydrogen peroxide (H2O2) production, which induces stress. Cell viability (MTT assay), change in intracellular reactive oxygen species (ROS), hydrogen peroxide (H2O2) level in media and gene expression (quantitative real time RT-PCR) were assessed in the models with and without the addition of samples. The ability of the samples to stimulate adipogenesis, glucose uptake, and adiponectin secretion as well as to attenuate GO-induced stress condition in differentiated 3T3-L1 adipocytes were also studied. The functional molecules present in the most active fraction (F2) of S. malaccense extract were identified to be myricetin derivatives (3.3 ± 0.05 % yield from the crude extract) particularly myricitrin. F2 showed significant improvement of antioxidant property compared to extract. It was an efficient nitric oxide scavenger. F2 was a better α-glucosidase inhibitor and exhibited significant α-amylase inhibition activity. F2 also inhibited formation of AGE, efficiently. GO and HG treatments induced stress in ARPE-19 cells by increasing intracellular ROS and H2O2 level in media. Significant cell death was observed with GO but not with HG treatment. F2 improved ARPE-19 cell viability by reducing intracellular ROS and H2O2 level induced by GO. It has also attenuated stress condition stimulated using HG. F2 exerted its protective effect by activating Nrf2 pathway and regulating various antioxidant enzymes, inflammatory and apoptotic factors at transcriptional level in both the stress models. In the adipocyte model, F2 exhibited significant ‘insulin-like’ effects as it was able to enhance adipogenesis, glucose uptake and adiponectin secretion, significantly. F2 activated insulin signaling pathway, adiponectin and AMPK signaling cascades besides attenuating stress condition in the 3T3-L1 model. S. malaccense leaf extract showed better protection than F2 against GO-induced stress condition developed in the differentiating 3T3-L1 cells by improving adipogenesis. The findings clearly reflected that the myricetin derivatives isolated from leaf extract of S. malaccense could attenuate oxidative stress and potentially serve as an adjuvant in the treatment of hyperglycemia and related complications.